(untitled) (Advancements in Homeopathic Research, 2024)
Objectives: The condition known as hypothyroidism occurs when the thyroid gland does not create enough thyroid hormone. Among women, it is the second most prevalent endocrine condition. Radiation therapy, thyroid surgery, and autoimmune diseases including Hashimoto’s thyroiditis are common causes. Hypothyroidism can cause infertility, abnormal menstruation, weight gain, changes in cognition, and exhaustion. Thyroid stimulating hormone is used to assess thyroid problems because it is extremely sensitive to thyroid malfunction. The traditional approach to treating hypothyroidism involves monotherapy with levothyroxine. In addition to conventional medicine, homoeopathy can be used to treat hypothyroidism.